Foreign Labour Migration and Utilization of Remittance in Nepal - K.C., Arjun (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
Migration in general refers to geographical or spatial mobility from one geographical unit to another which involves a change of place from the place of origin to the place of destination. Foreign labour as the form of the relationship of an employee on an employer outside the territory of the country where the employee pursues activity according to employer’s instructions for the remuneration agreed upon in advance. A remittance is a transfer of money by a foreign labour to an individual in his or her home country. Remittance to Nepal has a strong hold in the national economy and they have also transformed the lives of a large number of rural people. The objectives of the study are: to find the social background of the foreign labor migrants and to explore the utilization of remittance. This study overall uses quantitative method as core methodological analysis to substantiate its argument. The research method is survey with interview schedule as the tool. The study shows that there are different background of foreign labour migrants and most of the remittance is utilized to fulfill the livelihood, education and health. The implication of the study is to strengthen the foreign labour migration through the proper utilization of remittance in Nepal.